Review of the Internet of Things for Healthcare Monitoring - Mustafa, Twana; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2020)
These days, individuals are increasingly bound by indoor living, investing less energy outside. As a result, the importance of monitoring air quality inside to make indoor living progressively appropriate has risen immensely. The advancement of the Internet of Things (IoT) will significantly encourage patient analysis and monitoring procedures, as small IP-based wireless sensors can be placed on the patient's body. For example, one's blood pressure and coronary heart rate can be observed remotely and regularly using physiological parameters. Over the past few years, the IoT has experienced one of the most significant developments of the 21st century. The IoT describes a network of physical items, or 'things,' that are embedded with sensors, software, and other technologies that are able to connect and exchange data with other devices and systems over the internet. These devices range from ordinary household objects to sophisticated industrial tools. There are more than seven billion connected IoT devices today, and experts are expecting this number to grow to 10 billion by 2020 and 22 billion by 2025. This paper attempts to review and understand the utilization of the IoT in customized healthcare and how excellent healthcare can be acquired at a low cost. We will clarify, in brief, how the IoT functions and how wireless and sensing systems are utilized in order to carry out efficient healthcare applications. © 2020 IEEE.
8th International Symposium on Digital Forensics and Security, ISDFS 2020 -- 1 June 2020 through 2 June 2020 -- Beirut -- 161222
Keywords: Healthcare monitoring; Internet of Things (IoT); Wireless Body Area Network (WBAN); Wireless Personal Area Network (WPAN); Wireless Sensor Networks (WSN)